Cbl-b Deficiency in Mice Results in Exacerbation of Acute and Chronic Stages of Allergic Asthma - Carson, William F.; Guernsey, Linda A.; Singh, Anurag; Secor, Eric R.; Wohlfert, Elizabeth A.; Clark, Robert B.; Schramm, Craig M.; Kunkel, Steven L.; Thrall, Roger S. (Frontiers in Immunology, 2015)
Mice sensitized to ovalbumin (OVA) develop allergic airway disease (AAD) with short term daily OVA aerosol challenge; inflammation resolves with long-term OVA aerosol exposure, resulting in local inhalational tolerance (LIT). Cbl-b is an E3 ubiquitin ligase involved with CD28 signaling; Cbl-b-/- effector T cells are resistant to regulatory T cell mediated suppression in vitro and in vivo. The present study utilized Cbl-b-/- mice to investigate the role of Cbl-b in the development of AAD and LIT. Cbl-b-/- mice exhibited increased airway inflammation during AAD, which failed to resolve with long-term OVA aerosol exposure. Exacerbation of inflammation in Cbl-b-/- mice correlated with increased proinflammatory cytokine levels and expansion of effector T cells in the BAL during AAD, but did not result in either a modulation of lymphocyte subsets in systemic tissues or in OVA specific IgE in serum. These results implicate a role for Cbl-b in the resolution of allergic airway inflammation.